Optimal Delivery Management for the Prevention of Early Neonatal SARS-CoV-2 Infection: Systematic Review and Meta-analysis - Chan, Christina S.; Kong, Juin Yee; Sultana, Rehena; Mundra, Vatsala; Babata, Kikelomo L.; Mazzarella, Kelly; Adhikari, Emily H.; Yeo, Kee Thai; Hascoët, Jean-Michel; Brion, Luc P. (American Journal of Perinatology, 2024)
Objective Delivery management interventions (DMIs) were recommended to prevent delivery-associated transmission of maternal SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) to infants without evidence of effect on early neonatal SARS-CoV-2 infection (ENI) and neonatal death <28 days of life (ND). This systematic review describes different DMI combinations and the frequency of ENI and ND.Study Design Individual patient data were collected from articles published from January 1, 2020 to December 31, 2021 from Cochrane review databases, Medline, and Google Scholar. Article inclusion criteria were: documented maternal SARS-CoV-2 polymerase chain reaction (PCR)-positive status 10 days before delivery or symptomatic at delivery with a positive test within 48 hours, known delivery method, and known infant SARS-CoV-2 PCR result. Primary outcomes were ENI (positive PCR at 12 hours to 10 days) and ND. All characteristics were pooled using the DerSimonian–Laird inverse variance method. Primary outcome analyses were performed using logit transformation and random effect. Pooled results were expressed as percentages (95% confidence intervals). Continuity correction was applied for all pooled results if any included study has 0 event.Results A total of 11,075 publications were screened. 117 publications representing 244 infants and 230 mothers were included. All publications were case reports. ENI and ND were reported in 23.4% (18.2–29.18) and 2.1% (0.67–4.72) of cases, respectively. Among cases with available information, DMIs were reported for physical environment (85–100%), delivery-specific interventions (47–100%), and infant care practices (80–100%). No significant comparisons could be performed between different DMI combinations due to small sample size.Conclusion The evidence supporting any DMI in SARS-CoV-2-infected mothers to prevent ENI or ND is extremely limited. Limitations of this meta-analysis include high risk of bias, small sample size, and large confidence intervals. This identifies the need for multinational database generation and specific studies designed to provide evidence of DMI guidelines best suited to prevent transmission from mother to neonate.Key Points
Keywords: COVID-19; SARS-CoV-2; neonates; pregnancy; delivery management